(untitled) (The Strategic Review for Southern Africa, 2021)
Social movements often face the danger of becoming the very thing they are fighting against. This tension is evident within the student movement, Rhodes Must Fall, at the University of Cape Town. This dialectic is explored through the notion of 'alienation' as a concept of social philosophy. I argue that while the movement emerges from the experience of alienation, certain behaviours internal to the movement can also proceed to cause alienation. The lesson to be learnt from this contradiction is that we are all simultaneously oppressors and oppressed. From this emerges a positive understanding of alienation, as the experience of alienation is not only a negative one. One such positive lesson in this case is the alteration of our understandings of ourselves and others toward an all-inclusive liberation agenda. Failure to heed this could see the transformation potential of such movements like Rhodes Must Fall hijacked by hypocrisy.